Pickup and delivery costs: A proposed outsourcing model based on the number of stops - Kosovac Amel (Institut za istrazivanja i projektovanja u privredi, 2021)
The active introduction and modern technologies application in the transport market greatly affect all transport branches and the ways of their business. Availability and mass usage of the internet and Web services create a new ambiance of trade through online sales and e-commerce. The increase in internet sales has a direct effect on the business of courier companies. The number of shipments in the B2C (Business-to-Consumer) segment is growing and putting an increasing pressure on costs for companies that perform pickup and delivery. Companies are trying to adapt their business to the new challenges and conditions that prevail in the transport market through different cost management models. One way to manage costs is to outsource costs. This paper proposes a model cost calculation in outsourcing services for pickup and delivery shipments based on the number of stops.